(untitled) (Journal of Engineering, 2014)
This study produces an image of theoretical and experimental case of high loading stumbling condition for hip prosthesis. Model had been studied namely Charnley. This model was modeled with finite element method by using ANSYS software, the effect of changing the design parameters (head diameter, neck length, neck ratio, stem length) on Charnley design, for stumbling case as impact load where the load reach to (8.7* body weight) for impact duration of 0.005sec.An experimental rig had been constructed to test the hip model, this rig consist of a wood box with a smooth sliding shaft where a load of 1 pound is dropped from three heights. The strain produced by this impact is measured by using rosette strain gauge connected to Wheatstone bridge for the model .The signal is amplified and sent forward to a data acquisition and then saved in the connected laptop. From this study it is found that the changing in stem length had large effect on effective stress where the change in effective stress while stem length increased from (110mm to 140mm) was not more than (209MPa).